PELATIHAN TAJHIZUL MAYIT UNTUK MENINGKATKAN KESADARAN REMAJA SMP DALAM MERAWAT JENAZAH DI DESA SIBANGGOR JULU, PUNCAK SORIK MARAPI, MANDAILING NATAL - Putra Aulia; Annisa Wahyuni; Lilis Saadah; Nabila Amanda Putri; Salsa Nabila Hasan Nasution; Puja Puja; Ira Wardani Nst; Aisyah Harahap; Alawiyah Amini Nasution; Royhan Ansori Nasution; Ahmad Khoirur Rosyd (CV. Denasya Smart Publisher, 2025)
Training in tajhizul mayit is a very important form of religious education in efforts to improve the understanding and skills of the younger generation, especially teenagers and junior high school students, regarding the procedures for caring for the deceased in accordance with Islamic law. This community service activity was carried out in Sibanggor Julu Village, Puncak Sorik Marapi District, Mandailing Natal Regency. The activity aimed to instill awareness in junior high school students from an early age about the obligation to carry out fardhu kifayah, as well as to shape religious attitudes, social awareness, and a sense of social responsibility in the community. The methods used in this training included lectures, interactive discussions, and hands-on demonstrations covering bathing, shrouding, praying, and burying the deceased. Through this approach, participants not only gained theoretical knowledge but also practical experience that reinforced their understanding. The results of the activity showed a significant increase in the participants' knowledge, skills, and attitudes towards the importance of tajhizul mayit. In addition, this training also fostered spiritual awareness among the participants, strengthened their togetherness, and reinforced religious character values among junior high school students. Therefore, this program is expected to make a real contribution in nurturing a young generation that not only understands Islamic teachings, but is also ready to play an active role in social and religious life in the community.